PENDAMPINGAN PEMBUATAN PRODUK SAINS EDUKATIF BAGI MAHASISWA TERINTEGRASI PEMBELAJARAN PADA MATA KULIAH STM - Anggraeni, Desak Made; Katoda, Imelda Cindy; Kalli , Sesilia Inya (Antis-publisher, 2024)
This community service activity aims to assist students in developing and making simple educational science products based on an analysis of needs and the availability of resources in the surrounding environment. This PkM activity is carried out in 3 (three) stages, namely the preparation stage, implementation stage, and evaluation stage. Several methods are used to carry out activities, including observation, discussion, FGD, experimental, and presentation methods. This PkM activity was carried out in the Smart Room at Catholic University. This activity is carried out once a week, every Saturday from February 17 to March 16, 2024. 2 students assist. Participants in this activity were 20 (20) students from the physics education study program. The implementation of the mentoring activities went smoothly; activity participants gave positive responses regarding the implementation of the mentoring activities that had been carried out. This PkM activity can increase activity participants' knowledge, insight, and skills in developing simple educational science products that utilize various natural resources in the surrounding environment.